기업의 사회적 책임이 수출성과에 미치는 영향 - 김정심(Jeong-Sim Kim) (무역연구, 2016)
Corporate social responsibility (CSR) has received substantial attention from academics and practitioners over the past decades. Despite a great deal of literature on CSR, surprisingly few studies consider the impact of CSR on export performance. This issue is particularly of importance for the export-led Korean economy. To fill the gap, this paper examines whether CSR affects export performance. Constructing a panel dataset for 438 firms listed on the Korean stock market during the period between 2005 and 2014, we find that a firm’s CSR score is negatively associated with the ratio of export sales to total sales. This result is robust after employing Tobit analysis because export sales are left censored at zero, after using several control variables, and after considering the impact of the 2008 global financial crisis. In addition, increases in CSR scores lead to a decrease in export sales. Our results suggest that the active engagement in CSR is detrimental to export performance. Given the substantial rise in the importance of CSR all over the world, Korean firms should undertake serious efforts to connect their CSR activities with export performance. Furthermore, they should focus on CSR activities which effectively contribute to export performance. KCI Citation Count: 7